Environmental stewardship education in Tuvalu, Part 1: the role of policy Alignment - Tinilau, Soseala S.; Hemstock, Sarah L.; Mercer, Theresa G.; Hannaford, Matthew; Kythreotis, Andrew P. (MDPI, 2025)
Environmental stewardship is crucial for fostering sustainable development, particularly in vulnerable small-island developing states like Tuvalu. Government policies and frameworks play a vital role in shaping the education system, but inconsistencies in policy alignment often hamper efforts to embed Environmental Stewardship Education (ESE) into the national curriculum. We aimed to answer four questions: 1. What formal policies shape Environmental Stewardship Education (ESE) in Tuvalu? 2. Are national educational and environmental policies mutually consistent? 3. Are these national policies consistent with regional and global policies? 4. What challenges hinder the implementation of ESE in Tuvalu? These questions were addressed using a study of regional, international, and Tuvaluan online-available documentary assessments of national policies and frameworks in conjunction with those obtained from the Education Department. Our findings revealed that a combination of Tuvalu’s environmental and educational policies was instrumental in shaping ESE. Nationally, educational and environmental policies are internally inconsistent, as well as being inconsistent externally with regional and international policies. Recommendations for improving policy alignment and the sustainable integration of ESE into the curriculum are provided. The second part (Part 2) of our review covers the development and delivery of effective curricula for ESE.
Keywords: environmental stewardship; policy analysis; Tuvalu; national educational policies; regional policies; global policies; 3902 Education Policy, Sociology and Philosophy; 39 Education; 4 Quality Education